(untitled) (Research, Society and Development, 2021)
In Brazil, educational didactic models use occurred between the 1950s and 1980s, promoting teaching more effectively. Considering that didactic models are essential for understanding Botany contents, this work presents the didactic models use in the teaching of Botany from publications analysis in CAPES, SCIELO databases and in Annals of Congress platform National Botany-CNBot and National Education Congress-CONEDU, from 2005 to 2019. Specifically, it seeks to identify the effectiveness of using didactic models; teaching modalities in which they are used; materials for its production and methodologies used with Botany didactic model. The review showed that 32 publications met the inclusion criteria. The analyzed works present positive aspects regarding the didactic models use for botany teaching, as they support the understanding of theoretical concepts and comparison with the morphological studies of plants. Its use is made on a larger scale in Higher Education and Elementary Education. Biscuit is the recommended material for its production due to its durability and affordable price, but other materials can also be used. Didactic models are used during expository classes, practical classes, interactive classes, exhibitions, interventions and assist in the learning of visually impaired students.